DAMPAK COVID-19 TERHADAP PERILAKU KONSUMEN DALAM PENGGUNAAN MARKETPLACE DI INDONESIA - Muhammad Nur Fadillaha; M. Subchan (JURNAL MITRA MANAJEMEN, 2021)
AbstractThe prolonged situation of the Corona Virus Pandemic (Covid-19) has made changes in consumer behavior around the world, including in Indonesia. The limitation of community activities in fulfilling the need for daily products and services with PSBB makes people look for alternative shopping solutions through the marketplace to meet their daily needs, both goods and services. This situation is used by marketplace companies to increase the number of public spending transactions on their marketplace platforms. This is evident from many marketplace companies that have drastically increased their sales transactions. Keywords: Covid-19 Pandemic; Marketplace